2017
DOI: 10.1007/s11746-017-3009-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Intensity Ultrasound Frequency and High‐Speed Agitation on Fat Crystallization

Abstract: The objective of this research was to examine the effect of ultrasound frequency and high‐speed agitation on lipid crystallization. Interesterified soybean oil was crystallized at 44 °C without and with the application of high intensity ultrasound (HIU—20 and 40 kHz) or with high‐speed agitation (6000 and 24,000 rpm). Two tip amplitudes (24 and 108 µm) and three pulse durations were evaluated (5, 10, and 15 s) for the acoustic frequencies tested. Sonication at 20 kHz of frequency significantly reduced crystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 37 publications
5
26
0
3
Order By: Relevance
“…These studies showed that higher power levels have a greater effect on the induction of crystallization and on the reduction of crystal size. However, similar results to the ones reported in our study where a lack of effect of power level was reported by Silva et al (). It is possible that the lack of effect of the power level is due to the high melting point of the sonicated material, which is a common property of Silva's and our work.…”
Section: Resultssupporting
confidence: 94%
“…These studies showed that higher power levels have a greater effect on the induction of crystallization and on the reduction of crystal size. However, similar results to the ones reported in our study where a lack of effect of power level was reported by Silva et al (). It is possible that the lack of effect of the power level is due to the high melting point of the sonicated material, which is a common property of Silva's and our work.…”
Section: Resultssupporting
confidence: 94%
“…). Similar results on the effect of sonication on crystals sizes were observed in IESBO (Lee et al, ; Silva et al, ; Ye et al, ) and palm oil (Chen et al, ; Ye and Martini ).…”
Section: Resultssupporting
confidence: 75%
“…Crystallization can be modulated by external forces such as shear and cooling rate since they affect nucleation and crystallization kinetics (Blake & Marangoni, 2015). Recently, high-intensity ultrasound (HIU) with frequencies between 20 and 100 kHz has been introduced as a promising technique to modify microstructure of fat crystals (Silva et al, 2017). This technique could affect both primary and secondary nucleation of crystallization due to a phenomenon, called cavitation.…”
Section: Introductionmentioning
confidence: 99%